Sistem Pengendali Sistem Pintu Otomatis Berbasis Mikrokontroler Atmega 8535 - Ika Febriyanti Br Bangun (Jurnal Penelitian Rumpun Ilmu Teknik, 2023)
In the design of this tool, we designed a tool that is able to open and close the door automatically. To replace opening and closing manually using a PIR sensor (passive infrared). When someone is in the radius of the sensor, the door will open or close. We also use the Atmega 8535 micro, the reason we use the Atmega 8535 micro is because the Atmega 8535 micro already has an ADC (analogue digital converter) or analog to digital converter. Which serves as an input wave leveler to the microwave.